CLOVER: A modelling framework for sustainablecommunity-scale energy systems - Sandwell,P; Winchester,B; Beath,H; Nelson,J (The Journal of Open Source Software, 2023)
Sustainable Development Goal 7 aims to provide sustainable, affordable, reliable and modernenergy access to all by 2030 (United Nations, 2015). In order for this goal to be achieved,sustainable energy interventions in developing countries must be supported with design toolswhich can evaluate the technical performance of energy systems as well as their economic andclimate impacts.CLOVER (Continuous Lifetime Optimisation of Variable Electricity Resources) is a softwaretool for simulating and optimising community-scale energy systems, typically minigrids, tosupport energy access in developing countries (Winchester et al., 2022). CLOVER can be usedto model electricity demand and supply at an hourly resolution, for example allowing users toinvestigate how an electricity system might perform at a given location. CLOVER can alsoidentify an optimally-sized energy system to meet the needs of the community under specifiedconstraints. For example, a user could define an optimum system as one which provides adesired level of reliability at the lowest cost of electricity. CLOVER can provide an insightinto the technical performance, costs, and climate change impact of a system, and allow theuser to evaluate many different scenarios to decide on the best way to provide sustainable,affordable and reliable electricity to a community.CLOVER can be used on both personal computers and high-performance computing facilities.Its design separates its general framework (code, contained in a source src directory) fromuser inputs (data, contained in a directory entitled locations) which are specific to theirinvestigations. The user inputs these data via a combination of .csv and .yaml files. CLOVER’sstraightforward command-line interface provides simple operation for both experienced Pythonusers and those with little prior exposure to coding. An installable package, clover-energy, isavailable for users to download without needing to become familiar with GitHub’s interface.Informat